MOBLOG SEBAGAI KONVERGENSI NEW MEDIA - Tjahyana, Lady Joanne (Scriptura, 2008)
Moblog refers to blogging activities through mobile devices such as PDA and cell phone. Moblog is developed from previous well known computer used media application called blog. With the improvement of communication technology develop¬ment, mobile blog activity can be done through cellular phone. Moblog is a form of new media convergence, instead of old media convergence. This can be seen from new media’s charac¬teristics in moblogging that are Digitality, Interactivity, Disper¬sality, and Virtuality. Moblog is also combined from several new media applications and devices that are blog, cell phone, digital camera, internet, and several computer functions. There are several convergencies impli¬cations because of moblog that are media consumer behaviour, prosumer techonology production, and media ownership concentration. In conclusion, moblog is considered as a new media convergencies form that has some new media characters and gives some convergencies impact.